Unraveling the Psyche: A Critical Analysis of Historical and Contemporary Theories in Light of Neuroscientific Advances - Mir Mahmoud Seyyedvalilou; Marziye Alivandi Vafa; Seyed Mahmoud Tabatabaei (Iranian Journal of Educational Research)
Objective: It can be asserted that the interplay of psyche, mind, and awareness represents a paradox of totality and emptiness. The internal experience is intimately felt, akin to the neck vein, yet remains elusive, more distant than cosmic expanses. Humanity has long sought to deconstruct and understand the origins and essence of psychological phenomena. Shakespeare and Sartre highlight the significance of this inquiry. This study aims to analyze the philosophical and scientific theories regarding the mind's origins, roots, and nature, encompassing both pre and post-Renaissance perspectives and Neuroscience. Methods: The intention is to propose a conceptual-theoretical model that clarifies this phenomenon. A descriptive-analytical research methodology utilizing content analysis has been employed. Results: Findings reveal that before the Renaissance, the study of human nature was situated within philosophy, with psychology viewed as a branch thereof. However, the evolution of scientific psychology from the late nineteenth into the twentieth century paved the way for the Renaissance of Neuroscience, particularly from the 1970s onward, with significant advancements in understanding the mind through developmental theories and research findings. Conclusions: In conclusion, the mind is recognized as a sophisticated process integrating memory, intelligence, awareness, and philosophical consciousness, arising from complex cerebral interactions and neural dynamics. This creative inner reflection symbolizes the highest transcendent process, with the mind's diverse aspects emerging from the interplay of the brain, body, and existence throughout an evolutionary trajectory.